Challenges and opportunities for hybrid and improved forages: A seed market study in Kenya and East Africa - Florez, Fernando; Karimi, Peggy; Junca, John Jairo; Triana Ángel, Natalia; Burkart, Stefan (2024)
In East Africa and especially Kenya, forage is a primary food source for dairy cattle. Producers have traditionally used local forage varieties, but in recent years, there has been a notable increase in the adoption of hybrid and improved forages. The objective of this study is to analyze the dynamics of the hybrid and improved forage seed market in Kenya and other East African countries in recent years. Additionally, it aims to conduct a forward-looking analysis of the market's evolution over the next decade, identifying challenges and opportunities for improvement. We conducted 46 key informant interviews. We found a sustained growth in the improved forage seed market in recent years. The main challenges for further growth are high seed prices, regulatory difficulties, and limited farmer knowledge regarding forage selection and cultivation. Our findings reveal a virtuous cycle that could accelerate the adoption of hybrid and improved forages in East Africa: Research institutions are committed to the continuous improvement of existing varieties and the introduction of new strains through seed breeding and selection initiatives. Seed companies seek to increase their supply, while governments and development entities show interest in maintaining financial support and promoting the adoption of these forages. Alliances between producer associations and seed companies are emerging, aiming to offer seeds at more affordable prices to farmers. Finally, dairy farmers are interested in hybrid and improved forages due to their potential to increase milk production, optimize the use of farm space, and reduce vulnerability to climate change.